Collocational competence among Malaysian university students and their sources of errors - Mohd Rubani, Noranisa Afiqah; Rashid Ali, Farrah Diebaa; Badaruddin, Zuraidar (Academic Inspired Network, 2023)
This study investigated Malaysian ESL learners’ level of collocational competence and the source of their collocational errors. The subjects were 30 students from a local university in Malaysia. The research instrument was a Self-Completion Test (SCT) adopted from Huang (2001) that deliberates students’ knowledge of four types of lexical collocations: free combinations, restricted collocations, and figurative and pure idioms. The result showed that those participants could answer the questions from free combination category better than other categories because that category is the easiest category among all. On the other hand, the most difficult and challenging category is found to be the pure idioms category. For restricted collocations and figurative idioms, the respondents performed quite equally well in these both categories. Overall, the deviant answers given by respondents signified that Malaysian ESL learners are having inadequate knowledge of English collocations.